2003
DOI: 10.1002/jclp.10157
|View full text |Cite
|
Sign up to set email alerts
|

Therapist self‐disclosure: Research‐based suggestions for practitioners

Abstract: After defining therapist self-disclosure, we briefly discuss its theoretical foundations. We then move to our primary focus of presenting a number of suggestions for effective use of therapist self-disclosure, based on the extant empirical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(236 citation statements)
references
References 23 publications
7
227
0
2
Order By: Relevance
“…Advisors identified therapist self-disclosure as an effective and commonly used component of their clinical practice with Māori. The notion of utilising self-disclosure to facilitate a more personal therapeutic relationship with clients is consistent with current trends in international research, and several authors have found that a degree of therapist self-disclosure can have a positive impact on the therapeutic alliance and treatment outcome (e.g., Barrett & Berman, 2001;Knox & Hill, 2003). In the context of research into CBT with ethnic minority groups, the sharing of personal information between the therapist and client is encouraged as part of the initial engagement with Latino clients (Interian & Díaz-Martínez, 2007;Organista, 2006).…”
Section: Resultssupporting
confidence: 61%
“…Advisors identified therapist self-disclosure as an effective and commonly used component of their clinical practice with Māori. The notion of utilising self-disclosure to facilitate a more personal therapeutic relationship with clients is consistent with current trends in international research, and several authors have found that a degree of therapist self-disclosure can have a positive impact on the therapeutic alliance and treatment outcome (e.g., Barrett & Berman, 2001;Knox & Hill, 2003). In the context of research into CBT with ethnic minority groups, the sharing of personal information between the therapist and client is encouraged as part of the initial engagement with Latino clients (Interian & Díaz-Martínez, 2007;Organista, 2006).…”
Section: Resultssupporting
confidence: 61%
“…Some authors limit the notion of self-disclosure to verbal acts and differentiate types, such as facts, feelings, insight, strategy, reassurance/ support, challenge and immediacy (Knox & Hill, 2003). Zur, Williams, Lehavot, and Knapp (2009) concentrate less on the verbal content but view self-disclosure as the totality of information clients gain in contact with their therapists.…”
Section: The Rapist Self-disclosurementioning
confidence: 99%
“…Most studies elaborate on self-disclosure as a deliberate technique used by professionals for therapeutic reasons (Forrest, 2010;Knox & Hill, 2003). Attitudes towards therapist self-disclosure vary, however, between representatives of different modalities (Carew, 2009;Gibson, 2012).…”
Section: The Rapist Self-disclosurementioning
confidence: 99%
“…What is not known is the attitudes, skills, and behaviours of GPs. Psychologists are generally trained not to self-disclose, 4 likely as a result of the nature of the health issues they encounter in practice. 5 In medicine, there is limited empiric work into physician self-disclosure and it remains a controversial topic.…”
Section: Introductionmentioning
confidence: 99%